Development Of Chair Module In Web-Based Conference Management System - Rahadhitya Anuraga; Muharman Lubis; Ahmad Musnansyah (Electronic Integrated Computer Algorithm Journal, 2023)
Conferences are an important platform for academics, researchers, and practitioners to share knowledge and the latest research results. Efficient conference management is crucial in ensuring the success of such events. In this context, a Conference Management System (CMS) has emerged as a solution that facilitates various aspects of conference management. This research discusses the development of a Chair module in a web-based Conference Management System. The purpose of this research is to improve the efficiency and functionality of the Chair module so that it can better manage various aspects of the conference. Because in the existing application there are shortcomings in digital integration between organizers and information management that has not been centralized in one conference. The results showed that the development of the Chair module has worked as expected in the planning stage. The interaction between the Chair and conference participants, reviewers, and paper authors became more coordinated and integrated. The responsiveness of the web-based interface provides better accessibility, allowing the Chair to access information and make decisions in real-time.